Development of IDF Curve for Pontianak City Based on BRIN Rainfall Data During the 2014–2022 Observation Period - Hui, Sin; Soeryamassoeka, S. B.; Umar, Umar (Jurnal Teknik Sipil, 2025)
This study aims to develop an Intensity–Duration–Frequency (IDF) curve for Pontianak City using short-duration rainfall data recorded at the BRIN automatic weather station from 2014 to 2022. The RAPS consistency test confirmed that the data were statistically valid and suitable for hydrological analysis. Frequency analysis was conducted using several probability distributions, including Normal, Gumbel Type I, Log Pearson Type III, and Log-Normal (2- and 3-parameter), with the Normal distribution selected as the best fit based on goodness-of-fit and chi-square tests. Rainfall intensities were then calculated using the Mononobe method, with a locally calibrated sensitivity parameter m = 0.846. The resulting intensity equations for return periods of 2, 5, 10, 20, 50, and 100 years follow the exponential form I = a⋅t−0.846, where I is the rainfall intensity (mm/hour), t is the duration (minutes), and a is a return period–specific coefficient. The IDF curves demonstrate an inverse relationship between intensity and duration, confirming expected tropical rainfall behavior. These results provide a reliable tool for urban drainage design and flood risk assessment in Pontianak City